Decision-making supporting algorithm for choosing the duration of the audio communication session in a mobile ad-hoc network - Polshchykov, Kostiantyn; Lazarev, Sergej; Kiseleva, Elizaveta (Journal of the University of Zulia, 2019)
The article presents the research results on the development of the decision-making support algorithm for choosing the duration of audio communication sessions, which allows transmission of audio streams with a given quality level in a mobile ad-hoc network.The recommended communication session duration depends on the limiting number of packets in the audio stream, which is calculated based on the mathematical models, which describes the average volume of a multimedia message which can be transmitted in the given network parameters with the required quality. The proposed algorithm implementation will allow the ad-hoc node to display a message about the recommended audio communication session length.